1987
DOI: 10.1002/hep.1840070402
|View full text |Cite
|
Sign up to set email alerts
|

Plasma gaba, gaba-like activity and the brain gaba-benzodiazepine receptor complex in rats with chronic hepatic encephalopathy

Abstract: Plasma gamma-aminobutyric acid (GABA)-like activity, plasma GABA and the brain GABA-benzodiazepine receptor complex were studied in rats with chronic hepatic encephalopathy. Portal vein ligation (after prior subcutaneous transposition of the spleen) results in complete portal bypass of splanchnic blood. In addition, significant hepatocellular damage was superimposed on this model of portosystemic shunting by ligation of the common bile duct. Plasma GABA-like activity (determined by radioreceptor assay) and tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(21 citation statements)
references
References 25 publications
1
19
1
Order By: Relevance
“…16 To assess the efficiency of splenic transposition, we performed a preliminary time-course response in 20 mice. Both an anatomic exploration of new vessel growth and a functional response to total hepatic ischemia and reperfusion injury were determined.…”
Section: Discussionmentioning
confidence: 99%
“…16 To assess the efficiency of splenic transposition, we performed a preliminary time-course response in 20 mice. Both an anatomic exploration of new vessel growth and a functional response to total hepatic ischemia and reperfusion injury were determined.…”
Section: Discussionmentioning
confidence: 99%
“…This correspondence is illustrated also by the present control levels of GABA, which are within the range of levels of GABA con sidered as normal [5, 26. 34], However, in case of decreased liver function, the radiore ceptor assay may overestimate true GABA concentrations in plasma samples [23,32], Thus, determination of GABA by the radio receptor assay in plasma samples from a patient with fulminant hepatic failure yielded too high values due to interference of other markedly elevated amino acids, espe cially glutamine, with the assay [23]. Similar ly.…”
Section: Discussionmentioning
confidence: 99%
“…The high activity of GABA-degrading en zyme in the liver certainly explains the very short half-life (10-20 min) of systemically administered GABA [12]. Inhibition of pe ripheral GABA-T by drugs, such as y-vinyl GABA, y-acetylenic GABA, amino-oxyacetic acid or valproic acid, has been shown to cause 2-to 6-fold increases of plasma GABA levels, determined by ion exchange fluorometry or radioreceptor assay in rats, dogs or humans [21,[28][29][30][31], Similarly, 3-to 5-fold increases of plasma GABA have been found after portosystemic shunting by portal vein ligation in rats, using HPLC for plasma GABA analysis [32], Thus, decreased liver function and/or portosystemic shunting in humans will result in reduced peripheral GABA degradation and thereby in marked increases of plasma GABA produced by pe ripheral tissues and gut bacteria [3,5,6], Plasma GABA increases which have been reported previously for patients with acute or chronic hepatocellular disease vary con siderably, which, at least in part, may be due to methodological differences. Singh et al [6], who used a spectrophotometric method for GABA analysis, reported an about 3-fold plasma GABA increase in 40 encephalopathic patients with fulminant hepatic failure.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple attempts were carry out to find a model using a biliary ligation based technique -easy to perform-able to develop episodes of unambiguous hepatic encephalopathy. In this sense, a model was described in which encephalopathy was manifested after a portacaval anastomosis in cirrhotic rats by bile duct ligation, although this model was not widely distributed, probably because of the high mortality of the surgical shunt in cirrhotic animals (11). It has recently been proposed a model that combines bile duct ligation with rats fed with ammonia enriched diet, which have been found to increase the ammonia levels in the blood and in the brain (8) but the presence of behavioral changes in these animals, suggesting the development of encephalopathy, has not been found yet.…”
Section: Experimental Models For Hepatic Encephalopathymentioning
confidence: 99%
“…Different works have been recently published using a complete biliary ligation in rats with previous PCS, which induced an acute or subacute cholestasis (11). This model has not been fully characterized and has the added difficulty of inducing a severe weight loss, probably caused by anorexia or malabsorption.…”
Section: Portocaval Shunt With Additional Handlingmentioning
confidence: 99%